UMROH AS THE REASON FOR UNILATERAL TERMINATION OF EMPLOYMENT BY PT. DARUSSALAM BERLIAN MOTOR FROM THE PERSPECTIVE OF IJĀRAH BI AL-‘AMAL (Verdict Case Study No. 1/Pdt.Sus-PHI/2019/PN Bna) - Siti Azizah; Husni Mubarrak; Muslem Muslem (Universitas Islam Negeri Ar-Raniry, 2021)
PT. Darussalam Berlian Motor has terminated one of its employees on the grounds of performing the umroh. However the company/defendant argued that the employee/litigant had left their job without even notifying the defendant in advance. The defendat also explained that during their tenure, the litigant often made serious mistakes. On contrary, due to the serious mistakes that had been committed before, the defendant did not terminate the employment contract and the action was only taken when the litigant performed umroh in the holy land. The question in this research is how the judge considers the unilateral termination of employment experienced by the employee and what are the factors that cause the judge to grant the litigant’s claim. And how is the perspective of Ijārah bi al-‘Amal contract against the judge’s decision regardimg the grant of the litigant’s claim. In this research the authors used normative legal research method that analyzed the judge’s decree No. 1/Pdt.Sus-PHI/2019/PN Bna with qualitative approach. The judge in his decree considered thet the termination of employment on the grounds that the litigant had committed serious problems could not be considered because it was not in accordance with the applicable law. As for the factors that caused the judge to grant the litigant’s claim, due to the absence of evidence of a second PKWT contract between the litigant and the defendant, that’s why the previously PKWT contract changed to PKWTT contract. In Islamic law, when ones terminating a work relationship a company can perform fasakh through urbun which has similarities with the obligation to pay severance pay. From the explanation above, it can be concluded that unilateral termination of employment cannot be justified and does not have a string legal force.